2012
DOI: 10.1007/s10750-011-0977-9
|View full text |Cite
|
Sign up to set email alerts
|

Experimental silicon demand by the sponge Hymeniacidon perlevis reveals chronic limitation in field populations

Abstract: Dissolved silicon (DSi) is a key marine nutrient. Sponges and diatoms are relevant DSi consumers, but sponges appear to have a less efficient uptake system that requires higher ambient DSI concentrations for maximum uptake. We experimentally tested whether a sponge adapted to live at the intertidal (Hymeniacidon perlevis) also shows such a need for high DSi. Under laboratory conditions, sponges were exposed to both the natural DSi concentration (10 lM) and much higher levels (25, 40, and 70 lM) for 36 h, being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…In agreement with all previous sponge studies (Frøhlich and Barthel ; Reincke and Barthel ; Maldonado et al , ; López‐Acosta et al ), our results show important levels of between‐individual variability in the DSi consumption responses. While in the demosponges Axinella spp., T. citrina , and H. perlevis (Maldonado et al ; López‐Acosta et al ), the between‐individual variability was significantly related to sponge size and/or the particular physiological stage (i.e., reproductive vs. nonreproductive condition), a similar pattern has not been retrieved herein.…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with all previous sponge studies (Frøhlich and Barthel ; Reincke and Barthel ; Maldonado et al , ; López‐Acosta et al ), our results show important levels of between‐individual variability in the DSi consumption responses. While in the demosponges Axinella spp., T. citrina , and H. perlevis (Maldonado et al ; López‐Acosta et al ), the between‐individual variability was significantly related to sponge size and/or the particular physiological stage (i.e., reproductive vs. nonreproductive condition), a similar pattern has not been retrieved herein.…”
Section: Discussionsupporting
confidence: 93%
“…The results for H. perlevis in our study contrast with those obtained for intertidal individuals of this same species in the Yellow Sea (Dalian, China). When exposed at 10 (field DSi concentration), 25, 40, and 70 μM DSi during 36 h (Maldonado et al ), the Yellow Sea individuals showed consumption rates 3.3–5.7 times higher than the ones expected according to the H. perlevis kinetic equation obtained from the Brest population. In the current stage of knowledge, local adaptations in the performance of the sponge DSi utilization systems cannot be ruled out.…”
Section: Discussionmentioning
confidence: 97%
“…Maldonado et al. (, ) showed that spicule morphology and the presence or absence of a particular spicule type are influenced by seawater chemistry and the availability of nutrients such as silicic acid. Although microhabitat data were not collected as part of this study, we documented differences in spicule size among four different geographic locations, indicating environment plays a role in determining spicule morphology in Callyspongia .…”
Section: Discussionmentioning
confidence: 99%